PERBANDINGAN PERTUMBUHAN DAN PERKEMBANGAN GONAD IKAN MAS (Cyprinus carpio Linn.) DIPLOID DAN TETRAPLOID - Akhmad Taufiq Mukti (The East Java Biological Society, 2007)
The aim of this study were to know growth and gonadal development of tetraploidy common carp. The method that used in this study was experiment. Treatment that used was tetraploidyzation by heat shock 40°C during 1.5 minutes of common carp eggs to 29 minutes after fertilization. Five replicates were carried out for treatment. Parameters test were relative length growth (h), specific growth rate (SGR) and gonadal development of common carp. Data analysis that used was descriptive analysis. The result of this study indicated that tetraploidization teratment influenced on growth and gonadal development of common carp. The relative length growth of tetraploidy common carp was 5.38 ± 0.12 (30-days) and 19.12 ± 0.00 (110-days), as their specific growth rate was 19.87 ± 0.10% BW/day (30-days) and 8.57 ± 0.00% BW/day (110-days). Tetraploidy common carp have fertile characteristic and show gonadal development that same with diploid common carp relatively.